2016
DOI: 10.3945/an.115.010330
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Vitamin D Status on Offspring Brain Development and Function: a Systematic Review

Abstract: Various studies have examined associations between maternal vitamin D (VD) deficiency and offspring health, including offspring brain health. The purpose of this review was to summarize current evidence concerning the impact of maternal VD deficiency on brain development and function in offspring. A systematic search was conducted within Medline (on Ovid) for studies published through 7 May 2015. Animal and human studies that examined associations between maternal VD status or developmental VD deficiency and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…Another study conducted in Spain reported that infants of mothers with a concentration of 25 (OH) D3 at a pregnancy >30 ng/mL (>75 nmol/L) showed higher mental scores and psychomotor scores compared with mothers with a 25 (OH) D3 concentration <20 ng/mL or <50 nmol/L . However, other studies reported no relation between neonatal vitamin D status and neurocognitive development in infants …”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Spain reported that infants of mothers with a concentration of 25 (OH) D3 at a pregnancy >30 ng/mL (>75 nmol/L) showed higher mental scores and psychomotor scores compared with mothers with a 25 (OH) D3 concentration <20 ng/mL or <50 nmol/L . However, other studies reported no relation between neonatal vitamin D status and neurocognitive development in infants …”
Section: Discussionmentioning
confidence: 99%
“…The VD diffuses through the placenta from mother to the developing fetus. Therefore, maternal deficiency of VD is associated with fetal VD deficiency, as our results show in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…23 A cohort study in the United States assessing the relationship between cord blood vitamin D and developmental and cognitive achievement scores, showed that an increase in 5 nmol/L of vitamin D levels in the cord blood was associated with a very small increase in the Wechsler Intelligence Scale for Children (WISC) score at the age of seven years old. 8,24 Other study in Australia stated that cord blood vitamin D level had a positive association with language development in children aged 18 months and 4 years old, although the association was weak. 9 Thus, it could be concluded that vitamin D has an effect on child development, despite the weak association found on the currently available evidence.…”
Section: Discussionmentioning
confidence: 99%